Ethnomathematics-Based Flipbook E-Module - Clarine Aurellia; Yumira Simamora; Israq Maharani; Anjeli Malika Devani Tarigan (Universitas Suryakancana, 2026)
Mathematical literacy skills are an essential competency of the 21st century that demands innovation in digital teaching materials. Based on the needs analysis in the field, the use of interactive, self-contained web-based learning media still requires variations and has not explicitly integrated local cultural elements in the Data Centrality Measurement material. This study aims to produce a digital learning media prototype in the form of a flipbook e-module based on Deli Malay ethnomathematics assisted by the Heyzine platform integrated with the Discovery Learning flow, and to test the theoretical feasibility of the product. This type of research is a research and development (R&D) using the 4D model. In accordance with the limitations of the initial feasibility objectives, the development procedure is limited to the Develop stage in the theoretical validity testing phase by experts. Data collection techniques are carried out through documentation studies, structured interviews with teachers, and distribution of Likert scale assessment questionnaire instruments to experts. The assessment data are then analyzed quantitatively using the Aiken's V agreement index formula. The results of the development stage research indicate that the accumulated average content validity index of all learning device instruments is 0.92 with the criteria of Very Valid. In detail, the validity values were obtained from the Teaching Module instrument (0.88), LKPD (0.90), material aspects (0.91), flipbook media (0.94), cultural context (0.92), and the mathematical literacy ability test instrument which achieved the highest coefficient of 0.96. The conclusion of the study confirms that this ethnomathematics-based flipbook e-module product is declared valid, theoretically feasible, and recommended as a variation of independent teaching materials to support the achievement of 21st-century competency mathematics learning.